Molecular dynamics simulation on structure evolution of silica glass in nano-cutting at high temperature. Issue 13 (1st September 2020) - Liu, Changlin; Chu, Jianning; Chen, Xiao; Xiao, Junfeng; Xu, Jianfeng
ABSTRACT: Machining of silica glass is indeed a challenge due to its extreme brittleness and hardness. In recent years, laser-assisted machining (LAM) is becoming a powerful method for cutting silica glass. However, as a typical non-crystalline structure, the deformation mechanism of silica glass in the cutting process at high temperature has not been explored clearly. In this paper, classical molecular dynamics simulation was conducted to investigate the structure evolution of silica glass during the nano-cutting process at high temperature. Firstly, a uniaxial tension test was carried to investigate the brittle-to-ductile transition with increasing temperature. Then, the cutting simulation was conducted at 300 and 1500 K. The results showed that the plastic deformation is promoted at 1500 K. The atomic flow of silica glass is different from crystal material during the cutting process. No rotational flow and upward motion of atoms are observed. Moreover, microstructure evolution like bond-switch and rings distribution was discussed in detail. Furthermore, although the densification scope is almost unaffected, the extent of densification near the machined surface is greatly decreased at a high temperature. These results contribute to the theoretical research on the precision machining of silica glass with LAM.